2016
DOI: 10.3928/01484834-20161011-07
|View full text |Cite
|
Sign up to set email alerts
|

Simulation With Debriefing and Guided Reflective Journaling to Stimulate Critical Thinking in Prelicensure Baccalaureate Degree Nursing Students

Abstract: The LORAA and the HCTSR are effective measures of level of reflection and CT to evaluate learning from simulation and clinical experiences. [J Nurs Educ. 2016;55(11):645-650.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Mary et al. (2016) reported that the use of reflective diary method and scenario simulation method can independently promote the development of CT for nursing students. The simulation method gives nursing students the opportunity to develop clinical practice and communication skills and can guide them to adopt the method of reflective diary to assist nursing professional learning.…”
Section: Introductionmentioning
confidence: 99%
“…Mary et al. (2016) reported that the use of reflective diary method and scenario simulation method can independently promote the development of CT for nursing students. The simulation method gives nursing students the opportunity to develop clinical practice and communication skills and can guide them to adopt the method of reflective diary to assist nursing professional learning.…”
Section: Introductionmentioning
confidence: 99%
“…This could be observed in a study in which HC-TSR was applied to evaluate critical holistic thinking and clinical reasoning skills, with nursing undergraduate students through realistic simulations, with debriefing and guided reflexive diary to stimulate thinking. These practices showed effective measures to evaluate the level of reflection and critical thinking of academics (PADDEN et al, 2016). In this study, the importance of the assessment tool and its versatility in relation to the application are reaffirmed, since different teaching methodologies can be implemented to use HCTSR.…”
Section: Discussionmentioning
confidence: 73%
“…HCT is a guide articulating and unifying all the relevant elements of a patient's clinical and human situation. To think holistically is to consider the well-being of the patient as an integrated whole, not seeing it as a momentary clinical issue or problem to be treated or solved isolated from the whole of the person's health and the circumstances of life (PADDEN et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Journaling has been found to assist students reflect and articulate their thinking, assist in acquiring meta cognitive skills and help students to make conceptual or perceptual changes visible (Dunlap, 2006). It has also been found to be an effective teaching or learning method to develop critical thinking (Padden-Denmead et al, 2016). In guided journaling, the educator designs questions for students to reflect on their beliefs and assumptions about their own ESE.…”
Section: Critical Reflectionmentioning
confidence: 99%